Comprehensive Physiology 2001
DOI: 10.1002/cphy.cp070209
|View full text |Cite
|
Sign up to set email alerts
|

Production, Action, and Degradation of Somatostatin

Abstract: The sections in this article are: Anatomical Distribution of Somatostatin Cells Localization Pancreatic Somatostatin Cells Biosynthesis, Processing, and Intracellular Targeting Somatostatin Genes and Gene Products Regulation of Islet Somatostatin Regulation of Secretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 390 publications
1
16
0
Order By: Relevance
“…Further analysis of insulinopenic diabetic rats using streptozotocin has demonstrated an accumulation of SST peptides from the pancreas and upper gut [194]. It addition, the hyperplasia of δ-cells in the islet of diabetic patients has been associated with the loss of glucose receptors, which results in a two-to threefold production of SST in these organs [173]. Further implicating the importance of systemic SST-28 and SSTR5 in the regulation of insulin secretion and glucose homeostasis in diabetes is the fact that more than 30% of peripheral SST peptide is SST-28 and SSTR5 has 10-to 15-fold affinity specifically towards to SST-28.…”
Section: Sst and Sstrs In Type 1 Diabetesmentioning
confidence: 97%
See 1 more Smart Citation
“…Further analysis of insulinopenic diabetic rats using streptozotocin has demonstrated an accumulation of SST peptides from the pancreas and upper gut [194]. It addition, the hyperplasia of δ-cells in the islet of diabetic patients has been associated with the loss of glucose receptors, which results in a two-to threefold production of SST in these organs [173]. Further implicating the importance of systemic SST-28 and SSTR5 in the regulation of insulin secretion and glucose homeostasis in diabetes is the fact that more than 30% of peripheral SST peptide is SST-28 and SSTR5 has 10-to 15-fold affinity specifically towards to SST-28.…”
Section: Sst and Sstrs In Type 1 Diabetesmentioning
confidence: 97%
“…SST immunoreactivity has been located in the brain, peripheral nervous system, enteric and submucosal nerve plexi of the gut, the delta cells of the endocrine pancreas, thyroid and lymphoid tissue such as that of the thymus, spleen and lymph nodes [115][116][117][118]. In all tissues, including that of tumors, SST acts as an inhibitory hormone [95,103,144,173]. In some diseases, such as cutaneous T-cell lymphomas (Hodgkin's disease and non-Hodgkin's lymphomas), granulomatous diseases (tuberculosis, carcoidosis and Wegener's granulomatosis), rheumatoid arthritis and perhaps thymic tumors, cells have been shown to express a high density of SST receptors that can be visualized using radiolabeled octreotide [170,174,175].…”
Section: Sst and Sstrs In Type 1 Diabetesmentioning
confidence: 99%
“…It also has been shown that the cellular composition and location of cell types within the islets vary during development. 6 For example, C-cells constitute 40% of islet cells in the fetus and neonate, whereas the adult pancreas consists of 10% >-cells, 70% A-cells, 15% PP cells, and only 5% C-cells. 7,8 Delta cells have a granular appearance and have cytoplasmic processes that abut on islet capillaries.…”
Section: Pancreasmentioning
confidence: 99%
“…It is unknown whether a common or different mechanism activates the gene in different tissues. 6 In mice, the SST gene is first expressed on day 15 of embryonic development in cells that coexpress insulin, that is, later than the expression of glucagon (day 10) and insulin (day 12) genes. Insulin gene expression is later suppressed in cells that become mature SST-secreting C-cells.…”
Section: Somatostatinmentioning
confidence: 99%
See 1 more Smart Citation